The Impact of Price and Promotion towards Purchase Decision of Fast Fashion Brand in Offline Store - Verrelie, Michelle Clarissa; Agustiono, Agustiono (Universitas Ciputra Surabaya, 2022)
Since the COVID-19 pandemic, online shopping itself has become more popular, especially in fashion. Hopefully, the following research results can help solve the factors that influence buyers' decisions in fashion offline stores so that they can be a reference in an attempt to deal with the current situation. This research was conducted to analyze the impact of price and promotion on purchase decisions of fast fashion brands in offline stores mediated by brand image. This research is classified as quantitative research and SmartPLS will be used to calculate the statistical data. The population of this research is unknown and by purposive sampling method, the research sample is defined as fast fashion customers in offline stores in the past six months who live in West Surabaya with a total of 102 respondents who fulfilled the criteria through an online questionnaire collection based on 5-point Likert scale measurement. The result shows that price does not significantly affect purchase decisions. Meanwhile, promotion has a significant effect on purchase decisions. Brand image as the mediator also has a significant effect on purchase decisions. Brand image mediates price and promotion significantly towards purchase decisions.